Cheating behaviours among dental students in a dental school in South Kerala, India - Benley George; Deepthi PR; Vinod Mathew Mulamoottil; Sunu Alice Cherian; Jagan Lonappan; Ravi Rajan (Asian Pac. J. Health Sci., 2014)
Objective: The objective of this study was to investigate the clinical dental students’ attitudes about the seriousness of eleven cheating behaviours. Methods: A pretested self administered questionnaire was distributed to 155 undergraduate clinical students at Pushpagiri College of Dental Sciences in order to rate eleven commonly observed cheating behaviours. Results: The response rate was 100%. Four out of the eleven behaviours were considered as serious by more than 70% of the students. About 69% of the students consider themselves as somewhat ethical, while 26.5% considered themselves to be ethical and 4.5% considered themselves to be not ethical. Conclusion: This study reinforces the importance of the issue of cheating and how it is evaluated by dental students. Students considered certain behaviours to be serious cheating behaviours and others not serious cheating behaviours. Dental school authorities should ensure prompt and swift action is ensued against students engaging in cheating measures.